Hubungan Usia Menarche dan Status Gizi Siswi SMP Kelas 2 Dengan Kejadian Dismenore - Dita Trimayasari; Kadar Kuswandi (Jurnal Obstretika Scientia, 2014)
The research objective was to determine the relationship of age and nutritional status menarhce second grader with dysmenorrhea events SMP Negeri 1 Warunggunung in February of 2013". Design analytical research (quantitative) type of cross-sectional. Independent Variabels are age of menarche and nutritional status, and the dependent Variabel is dysmenorrhea. The population is all second grade students of SMP Negeri 1 Warunggunung many as 110 girls, while the sample is 53 grader 2. Instrument angket. Uji research is a statistic used is the Chi Square test to evaluate the level of signitifikasi or strength of the relationship. From these results it can be concluded that there was no correlation of age of menarche and nutritional status of grade 2 with the incidence of dysmenorrhea SMP Negeri 1 Warunggunung in February in 2013. Memperluas insight and knowledge on the relationship of age of menarche and nutritional status of class 2 with an incidence of dysmenorrhea SMP Negeri 1 Warunggunung in February of 2013.